Alternatives to regression models for estimating software projects - MacDonell, SG; Gray, AR (AUT University, 1996)
The use of ‘standard’ regression analysis to derive predictive equations for software development has recently been complemented by increasing numbers of analyses using less common methods, such as neural networks, fuzzy logic models, and regression trees. This paper considers the implications of using these methods and provides some recommendations as to when they may be appropriate. A comparison of techniques is also made in terms of their modelling capabilities with specific reference to function point analysis.